Tiling countertops with Michael Byrne - Byrne, Michael; Taunton Press ([Newtown, Conn. : Taunton Press], 1987)
Professional tilesetter Michael Byrne shows how to use traditional techniques and modern materials to tile a bathroom countertop. Shows how to work with both backer-board and mortar-bed substrates and how to lay ceramic tile around a sink.
"A Fine homebuilding DVD workshop."--Container.
Producer and director, Rick Mastelli ; editor, Nash Bly ; camera, Kevin Roche.
Keywords: Tile laying